The arrivals : a novel - Moore, Meg Mitchell (Little, Brown and Co., 2011)
Ginny and William's peaceful life in Vermont comes to an abrupt halt as their children and grandchildren descend one summer with an assortment of adult problems. By summer's end, the family gains new ideas of loyalty and responsibility, exposing the challenges of surviving the modern family--and the old adage, once a parent, always a parent, has never rung so true.